The implementation of a national strategy to encourage injury prevention program uptake in a community female sport in ireland: a camogie case study - O`Connor, S.; O`Brien, W.; Lacey, P. (International Sport Coaching Journal, 2022)
Community sports play an important role in maintaining sporting participation across all ages, from childhood to adulthood. Maintaining participation for females, however, can be a challenge. Injuries can negatively impact sporting participation, both in the short and long term. Thus, reducing the risk of injuries in community sports is essential. While there are developed injury prevention programs available, the uptake of such programs in community sports can be limited. Here, we outline how a female community sport in Ireland, namely, the Camogie Association, has developed and implemented an evidence-based strategy to improve the uptake of an injury prevention program nationally across all ages of their membership. We use the RE-AIM (Reach, Effectiveness, Adoption, Implementation and Maintenance) sports setting matrix as a guiding tool for evaluating this strategy. Varying settings and levels were targeted in this six-step implementation sequence, including the national sporting organisation, regional sporting organisations, alongside the individual coaches and players. The main outcomes of the strategy were that the Camogie Association formally adopted the developed injury prevention program (the Camogie Injury Prevention Program) and the adapted age appropriate programs from 8 years of age and upward. The Camogie Association also embedded this program within their coaching training course. The developed education workshop successfully improved coaches` attitudes and perceived ability to implement the Camogie Injury Prevention Program. The majority (72.5%) of coaches, 4 weeks after conducting the workshop, had implemented the program, and 95% felt the program could be maintained over multiple seasons. This program may provide guidance to similar national or regional sporting bodies that want to embed injury prevention programs within their respective governing body and maximise the implementation of an injury prevention program by their coaches and players.